Exploring the Appropriate Price of Semaglutide for Type 2 Diabetes Patients Based on Cost-Utility Analysis in China - Shanshan Hu; Shanshan Hu; Xiaorong Su; Xun Deng; Xun Deng; Yong Wang; Yong Wang (Frontiers Media S.A., 2021)
Introduction: Semaglutide is the first and only oral version of a glucagon-like peptide-1 analogue approved by the FDA for the treatment of type 2 diabetes (T2D). This research was designed to explore the appropriate price of once-weekly (OW) semaglutide for T2D patients in China based on cost-utility analysis.Methods: The baseline patient cohorts of OW semaglutide and once-daily (OD) empagliflozin were sourced from a patient-level meta-analysis integrating the SUSTAIN 2, SUSTAIN 3, SUSTAIN 8 and PIONEER 2 trials. The long-term health and economic outcomes were simulated using the United Kingdom Prospective Diabetes Study Outcome Model 2 from the Chinese healthcare provider's perspective. The appropriate price of semaglutide was explored by binary search. One-way sensitivity analysis (one-way SA), probabilistic sensitivity analysis and scenario analysis were applied to solve the uncertainty.Results: Under the assumption that the annual cost of semaglutide is equal to that of OD empagliflozin, OW semaglutide was superior to OD empagliflozin due to its higher quality adjusted life years and lower total costs. After binary search, the incremental cost-utility ratio of OW semaglutide vs. OD empagliflozin was approximately equal to 3λ with an annual cost of semaglutide of $1,007.18 and approximately equal to λ with an annual cost of semaglutide of $708.11. Subsequently, the incremental cost-utility ratio of OW semaglutide vs. OD empagliflozin was approximately 3λ and λ, with annual costs of semaglutide of $877.43 and $667.04, respectively, adjusted by one-way SA. Ultimately, the cost-utility results with annual costs of semaglutide of $877.43 and $667.04 were robust to probabilistic sensitivity analysis and scenario analysis.Conclusion: In conclusion, the annual cost of semaglutide appears to be appropriate between $667.04 and $877.43 for T2D patients in China.